Chitin nanowhisker-supported sulfonated poly(ether sulfone) proton exchange for fuel cell applications. (20th April 2016) - Zhang, Chan; Zhuang, Xupin; Li, Xiaojie; Wang, Wei; Cheng, Bowen; Kang, Weimin; Cai, Zhanjun; Li, Mengqin
Highlights: Chitin nanowhiskers (CNW) were prepared by TEMPO mediated oxidation of α-chitin. CNW supported sulfonated poly(ether sulfone) membrane was gained by solution casting. CNW were well dispersed in the sulfonated poly(ether sulfone) (SPES) matrix. SPES/CNW membranes showed outstanding performance as PEMs. Abstract: To balance the relationship among proton conductivity and mechanic strength of sulfonated poly(ether sulfone) (SPES) membrane, chitin nanowhisker-supported nanocomposite membranes were prepared by incorporating whiskers into SPES. The as-prepared chitin whiskers were prepared by 2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical (TEMPO) mediated oxidation of α-chitin from crab shells. The structure and properties of the composite membranes were examined as proton exchange membrane (PEM). Results showed that chitin nanowhiskers were dispersed incompactly in the SPES matrix. Thermal stability, mechanical properties, water uptake and proton conductivity of the nanocomposite films were improved from those of the pure SPES film with increasing whisker content, which ascribed to strong interactions between whiskers and between SPES molecules and chitin whiskers via hydrogen bonding. These indicated that composition of filler and matrix got good properties and whisker-supported membranes are promising materials for PEM.